“Utilización de diferentes niveles de harina de cáscara de plátano (musa paradisiaca) en sustitución parcial de carbohidratos para la alimentación de pollos broiler” - Chasipanta Erique, Johanna Mishell (2023)
In the present investigation, the feasibility of using banana peel flour to partially replace corn as part of the diet for broilers was evaluated, providing new food alternatives, to obtain a product that reduces production costs without altering the productive parameters. One hundred chickens of the Cobb500 line, three days old, with an average body weight of 70.5 grams, were used, which were randomly divided into 4 groups consisting of 25 chickens in each group, and 5 repetitions per group. The treatments were distributed as: T0 (control treatment - base diet), T1 (base diet + 0.5% addition of banana peel meal), T2 (base diet + 1% addition of banana peel meal), T3 (Basic diet + 1.5% addition of banana peel meal). The bromatological, microbiological and physical characterization of the banana peel flour was carried out to verify its composition and properties. This investigation lasted 42 days and weekly data on weights and daily consumption were collected for further analysis. Analysis of variance (ANOVA) and a 5% Duncan test were performed to differentiate between treatments. In the results analysis stage, We found that the parameters of weight gain and food consumption, T3 was better with 894 grams and 1458 grams; in the feed conversion rate variable, T0 was better. According to the benefit/cost factor, T0 made a profit of 0.12 cents per chicken, whereas T1 and T3 made 0.02 and 0.03 cents. Banana peel meal can be utilized as an alternate feed for broilers because the data gathered show that there were no statistically significant differences between the four treatments.